Eating disorders risk assessment and body esteem among elite polish contact karate athletes - Dobkowska-Szefer, D.; Staskiewicz-Bartecka, W.; Kiciak, A.; Kardas, M. (Frontiers in Nutrition, 2025)
Background: The prevalence of disordered eating behaviors and body image disturbances among athletes in weight-category sports remains insufficiently explored, especially in combat disciplines such as contact karate. The present study aimed to assess the risk of eating disorders and body image perception among elite Polish contact karate athletes, considering the influence of competitive pressure, weight-category requirements, and body image ideals on nutritional behaviors and mental health.